Novel albendazole–chitosan nanoparticles for intestinal absorption enhancement and hepatic targeting improvement in rats1. Issue 6 (26th March 2013) - Liu, Yang; Wang, Xiao‐qing; Ren, Wei‐xin; Chen, Yuan‐lan; Yu, Yang; Zhang, Jian‐kang; Bawudong, Dilimulati; Gu, Jun‐peng; Xu, Xiao‐dong; Zhang, Xue‐nong
Abstract: To improve the treatment of helminthiasis, filariasis, and colorectal cancer, albendazole‐associated chitosan nanoparticles (ABZ‐CS‐NPs) were prepared using the emulsion crosslinking volatile technique with contained sodium tripolyphosphate as the crosslinking agent and Poloxamer 188 as the auxiliary solvent. The structural characteristics of the NPs were determined using X‐ray diffraction to analyze the interaction between CS and the drug. The NPs were then evaluated in terms of their physicochemical characteristics, drug release behavior, in vivo pharmacokinetic parameters, and biodistribution in animal studies. ABZ‐loaded NPs with a uniformly spherical particle sizes (157.8 ± 2.82 nm) showed efficient drug loading, encapsulated efficiency, and high physical stability. The drug release from ABZ‐CS‐NPs was extended over several periods. Kinetic models were then fitted to determine the release mechanisms. ABZ and its metabolite albendazole sulfoxide (ABZSX) were analyzed in rats with mebendazole as the internal standard using reversed‐phase high‐performance liquid chromatography. Compared with the ABZ suspension groups, the relative bioavailability values of ABZ and ABZSX were 146.05 and 222.15%, respectively. In addition, the plasma concentration versus time curve is consistent with that of the two compartment models in the plasma concentration versus time curve. The results indicate that the ABZ‐loaded NPs are promising novel ABZ candidates for passive diffusion in the treatment of hydatid cysts in the liver via oral administration. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.